2015
DOI: 10.1097/bot.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Hemiarthroplasty for Proximal Humerus Fracture Are Significantly Affected by Hand Dominance

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…These data coincide with the observations of Diklić et al [10] whose research showed that the dominant hand was affected in 62% of 29 patients, as well as with other literature data where a fracture of the proximal humerus frequently occurs in the dominant hand [9,14]. LeBlanc et al [15] in their work wondered whether there was a difference in the treatment outcome of fractures of the proximal humeral treated with hemiarthroplasty in relation to whether the dominant or non-dominant arm was affected. Their study included 61 patients with a multifragmented fracture of the proximal humerus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data coincide with the observations of Diklić et al [10] whose research showed that the dominant hand was affected in 62% of 29 patients, as well as with other literature data where a fracture of the proximal humerus frequently occurs in the dominant hand [9,14]. LeBlanc et al [15] in their work wondered whether there was a difference in the treatment outcome of fractures of the proximal humeral treated with hemiarthroplasty in relation to whether the dominant or non-dominant arm was affected. Their study included 61 patients with a multifragmented fracture of the proximal humerus.…”
Section: Discussionsupporting
confidence: 90%
“…The maximum score for the presence and intensity of pain is 15 points, 20 points for the activity level, 40 points for the range of motion and 25 points for the strength of abduction. The difference in the Constant shoulder score between the healthy and operated limb represents a Constant's result which can be excellent (<11), good (12)(13)(14)(15)(16)(17)(18)(19)(20), fair (21-30) and poor (> 31).…”
Section: Methodsmentioning
confidence: 99%
“…Brostrom et al 16 in 1992 stated that TSA performed in the DO extremity fared worse compared to the ND extremity without further data analysis. LeBlanc et al 17 found poorer outcomes in the dominant extremity when a hemiarthroplasty was performed for proximal humerus fractures. Conversely, Cvetanovich et al 19 found that dominant shoulders attain increased FE compared to their nondominant cohort when an anatomic TSA was performed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, previous studies analyzing shoulder arthroplasty surgery have commented on hand dominance and its association with inferior clinical outcomes. 16,17 To our knowledge, no studies have evaluated the effects of hand dominance on patient outcomes and postoperative range of motion (ROM) after rTSA. We hypothesize that surgery for the dominant (DO) or nondominant (ND) extremity will result in equivalent changes in patient outcomes and shoulder ROM.…”
Section: Introductionmentioning
confidence: 99%
“…Further, other factors that are associated with outcomes after HA include age, hand dominance, rotator cuff status, and implant type. [25][26][27][28][29] Because proximal humerus fracture-dislocations and head-split fractures have a notoriously high rate of osteonecrosis and hardware complications, 11,13,30 they often present a treatment dilemma for surgeons, especially in young patients where preservation of native anatomy and avoidance of arthroplasty is preferable. This study sought to evaluate the clinical outcomes and health-related quality of life scores when treating patients with these injuries.…”
Section: Discussionmentioning
confidence: 99%